2021
DOI: 10.1021/acs.jmedchem.1c00578
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of N-Phenylpropenoyl-l-amino Acids as Potent and Selective Inducible Nitric Oxide Synthase Inhibitors for Parkinson’s Disease

Abstract: N-Phenylpropenoyl-L-amino acids (NPAs) are inducible nitric oxide synthase (iNOS) inhibitors possessing preventive effects for Parkinson's disease (PD). Here, structural modifications for improving the iNOS inhibitory activity and blood−brain barrier (BBB) permeability of NPAs were conducted, leading to 20 optimized NPA derivatives (1−20). Compound 18, with the most potent activity (IC 50 = 74 nM), high BBB permeability (P e = 19.1 × 10 −6 cm/s), and high selectivity over other NOS isoforms, was selected as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…4-Trifluoromethyl-( E )-cinnamoyl]- L -4- F -phenylalanine acid ( AE-18 ; Figure A), which was synthesized in our previous study, has been demonstrated to provide therapeutic effects in the MPTP/probenecid-induced chronic PD model through the DAergic neuronal repair pathway . In parallel, post-modeling administration of AE-18 in the midbrain ischemia-reperfusion model was also shown to reduce neurological damage, reduce infarct volume, and improve motor disturbance by increasing VEGF and BDNF levels .…”
Section: Introductionmentioning
confidence: 99%
“…4-Trifluoromethyl-( E )-cinnamoyl]- L -4- F -phenylalanine acid ( AE-18 ; Figure A), which was synthesized in our previous study, has been demonstrated to provide therapeutic effects in the MPTP/probenecid-induced chronic PD model through the DAergic neuronal repair pathway . In parallel, post-modeling administration of AE-18 in the midbrain ischemia-reperfusion model was also shown to reduce neurological damage, reduce infarct volume, and improve motor disturbance by increasing VEGF and BDNF levels .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 3D-QSAR modeling has been successfully applied to virtually select novel inhibitors on the basis of structure-property relationships from the ligand view. 34,35 In addition, molecular dynamics simulation has been widely employed to study the binding mode of potential inhibitors in the active site of the target for designing new compounds. 36,37 These studies provide valuable clues for drug design, while the MM MD simulations are usually used to capture static binding for the target ligand in the binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 8 attenuated LPS-induced neuroinflammation by hindering the overexpression of NO and IL-1β . Compounds 9 and 10 functioned as iNOS inhibitors, providing relief from neuroinflammation. , Considering the anti-inflammatory capacity of coixol, we revealed two series of coixol derivatives combined with cinnamic acid and explored their anti-inflammatory activities in vitro and in vivo in this work.…”
mentioning
confidence: 99%